Mendidik Generasi Unggul: Mengintegrasikan Manajemen Mutu dan Nilai-Nilai Islam dalam Pendidikan di Mis Guppi 13 Desa Tasik Malaya Rejang Lebong - Aprida, Oma; Trinanda, Ririn; Warlizasusi, Jumira; Sahib, Abdul (Indonesian Journal of Islamic Educational Management, 2024)
Islamic education has a significant role in shaping the character and morality of future generations. In facing the challenges of globalization, integration between quality management and Islamic values becomes relevant to ensure holistic educational quality. This research aims to reveal the concept of integration between quality management and Islamic values in education, with a focus on MIS GUPPI 13 Tasik Malaya Village, Rejang Lebong. This research uses a qualitative approach. Research informants consisted of teaching staff, students and parents at MIS GUPPI 13. Data collection techniques included participant observation, in-depth interviews and document analysis. Data were analyzed inductively to identify patterns of findings. The research results show that the integration of quality management and Islamic values at MIS GUPPI 13 Tasik Malaya Village, Rejang Lebong, creates a holistic educational environment. The curriculum, which is prepared by taking into account Islamic values as a philosophical basis, has succeeded in producing graduates who are not only academically competent but also have noble character. This integration has a positive impact on the formation of student character and positive contributions to the surrounding community